Implementasi Model Kepemimpinan Situasional: Kebijakan Merdeka Belajar Tentang Relaksasi Dana Bos Dan Dampaknya Terhadap Aksesibilitas Pendidikan - Novrian Satria Perdana (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
The objectives of this study include: 1) To examine the independent policy of learning about the relaxation of BOS funds according to situational leadership theory; 2) Analyzing the impact of the policy on the realization of the policy of relaxing BOS funds on the accessibility of education (participation and level of completion of education) during the covid 19 pandemic. The unit of analysis of this research is the policy of relaxation of BOS funds at the level of SD/equivalent, SMP/equivalent, SMA/K/equivalent . This study uses a mixed methods approach, which uses a literature review to answer the first research objective, and uses secondary data analysis sourced from the Central Statistics Agency to answer the second research objective. Based on the literature review and secondary data analysis, this study concludes: 1) The Mendikbudristek leadership model is in line with the S2 (Selling-Coaching) leadership style. The Minister of Education and Technology establishes a policy of independent learning as stated in Permendikbud Number 8 and Number 19 of 2020 as a form of high direction and support behavior in responding to the covid pandemic situation to make it easier for schools to spend the BOS budget so that the learning process can be optimal; 2) The use of BOS funds in the majority of schools has followed the mechanism established by the Minister of Education and Technology in the Free Learning program: Relaxation of BOS Funds. BOS funds are proven to have a correlation with education accessibility and have a positive impact.